ENTREPRENEURIAL ORIENTATION AND BUSINESS PERFORMANCE OF SMALL-SCALE ENTERPRISES IN SOUTH-EAST NIGERIA (Journal of the Management Sciences, 2025)
This study examined how entrepreneurial orientation (EO) influences the performance of small-scale enterprises in South-East Nigeria. The study adopted a descriptive survey methodology. Quantitative data were collected from 379 business owners and managers out of a population of 7,061 across Abia, Anambra, Ebonyi, Enugu, and Imo states. The study was anchored on the Dynamic Capabilities Theory which posits that in rapidly changing environments, a firm's sustained competitive advantage comes from its ability to continuously reconfigure and renew its capabilities. The focus of the study was on selected three key EO dimensions: risk-taking, competitive aggressiveness, and proactiveness. The findings revealed a significant positive relationship between these entrepreneurial traits and business performance. Entrepreneurial risk-taking was strongly linked to improved financial stability, indicating that small businesses willing to engage in calculated risks are better positioned for long-term financial resilience. Competitive aggressiveness emerged as critical for business survival, emphasizing the importance of assertive market strategies in highly competitive environments. Additionally, entrepreneurial proactiveness significantly enhanced market share, highlighting the value of anticipating market trends and innovating ahead of competitors. The study concludes that adopting a robust entrepreneurial mindset, characterized by calculated risk-taking, competitive aggressiveness, and proactiveness, is vital for small business performance in South-east Nigeria. Such an approach enables these businesses to thrive, sustain themselves, and grow.
Keywords: Entrepreneurial Orientation; Business Performance; Small scale Enterprises